2014
DOI: 10.1088/0004-637x/785/1/64
|View full text |Cite
|
Sign up to set email alerts
|

WHAT IS THE PHYSICAL ORIGIN OF STRONG Lyα EMISSION? I. DEMOGRAPHICS OF Lyα EMITTER STRUCTURES

Abstract: We present the results of structure analyses for a large sample of 426 Lyα emitters (LAEs) at z ∼ 2.2 that are observed with HST/ACS and WFC3-IR by deep extra-galactic legacy surveys. We confirm that the merger fraction and the average ellipticity of LAE's stellar component are 10 − 30% and 0.4 − 0.6, respectively, that are comparable with previous study results. We successfully identify that some LAEs have a spatial offset between Lyα and stellar-continuum emission peaks, δ Lyα , by ∼ 2.5−4 kpc beyond our sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
65
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 84 publications
13
65
0
Order By: Relevance
“…was about 0.6, suggesting the presence of elongated structures due to merging activity or clumps of star formation. However, Shibuya et al (2014) found that the LAEs in their sample with EW(Lyα) > 100 Å tended to be characterized by a small ellipticity both in the rest-frame UV and optical. This is supported by the theoretical results of Verhamme et al (2012) and Laursen et al (2009), which showed that Lyα photons could more easily escape from face-on disks (ellipticity ∼0), generally characterized by low column density of HI along the line of sight.…”
Section: Ellipticity and Clumpinessmentioning
confidence: 86%
See 2 more Smart Citations
“…was about 0.6, suggesting the presence of elongated structures due to merging activity or clumps of star formation. However, Shibuya et al (2014) found that the LAEs in their sample with EW(Lyα) > 100 Å tended to be characterized by a small ellipticity both in the rest-frame UV and optical. This is supported by the theoretical results of Verhamme et al (2012) and Laursen et al (2009), which showed that Lyα photons could more easily escape from face-on disks (ellipticity ∼0), generally characterized by low column density of HI along the line of sight.…”
Section: Ellipticity and Clumpinessmentioning
confidence: 86%
“…Late-stage mergers could instead be characterized by turbulent star-formation episodes and, as a consequence, patchy Lyα emissions, just like the ones observed within one galaxy with numerous star-forming regions. This may indicate that the clumpy Lyα emitting galaxies observed at high redshift (Bond et al 2012;Gronwall et al 2011;Shibuya et al 2014) could also be experiencing early-stage merging events (Cooke et al 2010). Of the twelve LARS galaxies, whose continuum morphologies are consistent with them being merging systems, six are LAEs.…”
Section: Local Universe Larsmentioning
confidence: 97%
See 1 more Smart Citation
“…The clear advantage that Lyα photons take of the bipolar outflowing halos of Mrk 1486 to easily escape from this object suggests that the same mechanism may be at work in a large number of highly inclined disk galaxies that are observed at low-z and high-z. This may require a critical review of the strong observational biases in surveys of high-z Lyα-emitting galaxies (as edge-on disk galaxies are also detected as LAEs; Shibuya et al 2014) and the robustness of the viewing angle effect on the Lyα properties of disk galaxies. in the 3D geometry Fig. A.1.…”
Section: Discussionmentioning
confidence: 99%
“…Given the clear advantage Lyα photons take of the outflowing halos of Mrk 1486 to easily escape toward the observer, we may generalize this mechanism to a large number of edge-on disk galaxies. In particular, this may explain the origin of very bright Lyα emission lines observed from elongated disk objects at high redshift (Shibuya et al 2014). In conclusion, this mechanism may challenge the strong observational biases in surveys of Lyα-emitting galaxies (as edge-on disk galaxies might also be detected as LAEs) and the robustness of the viewing angle effect on the Lyα properties of disk galaxies (Laursen & Sommer-Larsen 2007;Verhamme et al 2012;Behrens & Braun 2014).…”
Section: Hi and Dust Clumpiness Inside The Disk And The Outflowing Halosmentioning
confidence: 94%